Pengelolaan Anggaran Pendapatan dan Belanja Desa Ditinjau dari Partisipasi Masyarakat dan Transparansi di Kecamatan - Dimas Arrisky; Rita Martini; Yevi Dwitayanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this quantitative research is to determine the influence of Community Participation and Transparency on APBdes. Initial data was obtained from a questionnaire. According to this research, the population consists of six villages in Talang Kelapa District. In this research, purposive sampling technique was used to take 130 individuals as samples. uses purposively chosen criteria to determine topics deemed relevant. The SmartPLS 4.0 program is used to complete data analysis tools with measurement model evaluation and structural model evaluation. This research found that the Community Participation variable makes a significant contribution to the management of village income and expenditure budgets. The transparency variable also makes a significant contribution to the management budget.